Improving Service Quality Through Strengthening Transformational Leadership, Technology Literacy, Creativity, Interpersonal Communication and Entrepreneurship - Jayadih, Jayadih (The Islamic Education and Multiculturalism Foundation, 2024)
The purpose of this study is to produce strategies and ways to improve the quality of teacher services at the private Vocational High School (SMK) level by examining other variables that positively affect the quality of teacher services in educating and teaching their students. Furthermore, the strategies and ways to improve the quality of services found were used as recommendations to related parties, namely the Head of the Education Office, School Supervisors, Foundations, School Principals, and Private Vocational Teachers in South Tangerang City. Finding the best model to improve the quality of teacher services by conducting empirical research through the Modeling and Optimization of Resource Managemen method. This research method using the POP-HR method (Modeling and Optimization of Management Resource Strengthening) is a research approach that runs sequentially and exploratorily, which begins with a research study on Service Quality. In this study, a gap between real and ideal conditions of teacher behavior as an indicator of service quality was identified. The next stage involves qualitative research in the form of interviews with informants to explore the factors that affect the quality of teacher services and the relationship between these factors. The results of this study show that Based on the survey results, factors were found to improve the quality of teacher services as follows: 1) Transformational Leadership, 2) Technology Literacy, 3) Creativity, 4) Interpersonal Communication, and 5) Entrepreneurship.